Looking for Insights: A Comparison of Secondary Education English Curricula in Indonesia and Estonia - Arta, Berli; Kholis, Adhan; Rahayu, Rahayu; Azmi, Ulul; Lisan, Khusnul Harsul (Universitas Islam Sultan Agung, 2023)
Both Indonesia and Estonia have similar contexts of learning English as a foreign language. The learning achievements reveal a considerable disparity when considering the worldwide assessment of English proficiency, with Indonesia ranking 79th and Estonia securing the 23rd position according to the (EF English Proficiency Index in 2023). This study compares English curricula in Indonesia and Estonia, examining the differences between them despite similar conditions for teaching English as a foreign language. The fundamental goal of the study was to identify the factors that influence diverse learning outcomes in various countries. The study used content analysis to compare curricular papers from both countries on six critical criteria including: (1) stakeholders involved in English curriculum development, (2) stakeholders' reactions to the English curriculum, (3) stated purposes of the curriculum, (4) educational philosophies underlying the English curricula, (5) unstated purposes of the curricula, and (6) influential factors shaping the curricula. The analysis suggested that the key drivers to the discrepancy in learning results in both countries were national policy, pedagogy, and assessment implementations. The results showed that the main result of the mentioned alterations underscored the need for an enhanced approach to the instruction and acquisition of English. Allocating sufficient time for English learning allows students to maximize their opportunities for developing language skills. Moreover, integrating speaking and writing elements into final evaluations and embracing a communicative language strategy can inspire both educators and learners to participate in more genuine learning experiences.